2003
DOI: 10.1634/stemcells.21-1-98
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐Specific Gene Expression in Cultured Human Hematopoietic Stem Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 33 publications
(44 reference statements)
4
59
0
1
Order By: Relevance
“…There have been a number of studies suggesting that bone marrow-marrow progenitor cells may differentiate into hepatocyte-like cells in rodents (18)(19)(20)(21)(22). Studies utilizing human bone marrow-derived cells have produced similar results both in vitro and in animal studies (17,(23)(24)(25); however, the phenotype of the hepatocyte-like cells has not been adequately defined in most cases, and the demonstration of cellular fusion (26,27) posed a major limitation to the interpretation of animal transplantation studies. Human umbilical cord blood has also been suggested to be a reliable source of transplantable hepatic progenitor cells (15), and some limited attempts have been made to demonstrate that these cells can differentiate without cellular fusion (28).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies suggesting that bone marrow-marrow progenitor cells may differentiate into hepatocyte-like cells in rodents (18)(19)(20)(21)(22). Studies utilizing human bone marrow-derived cells have produced similar results both in vitro and in animal studies (17,(23)(24)(25); however, the phenotype of the hepatocyte-like cells has not been adequately defined in most cases, and the demonstration of cellular fusion (26,27) posed a major limitation to the interpretation of animal transplantation studies. Human umbilical cord blood has also been suggested to be a reliable source of transplantable hepatic progenitor cells (15), and some limited attempts have been made to demonstrate that these cells can differentiate without cellular fusion (28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been undertaken mostly in rodents [7,9,[14][15][16][17], but in humans, bone marrow [8,[18][19][20], amniotic tissue [21], cord blood [22], and adult and fetal liver have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Studies identifying potential stem cells with hepatic markers derived from bone marrow described by Fiegel et al showed albumin and CK-19 expression by RT-PCR only after culture in a collagen matrix for 35 days [18], and Jiang et al also noted the differentiated phenotype after many weeks in culture [32].…”
Section: C) Cells Expressed Cytokeratins Suggestive Of Hepatocytes (Cmentioning
confidence: 99%
“…16 To investigate whether MBL is synthesised by CD34 þ cells, mononuclear cells were obtained from three BM samples (donors with MBL wild type) and CD34 þ cells were separated and cultured as described earlier. 17 MBL concentrations in cultures were analysed on day 14 using the ELISA.…”
Section: Patientsmentioning
confidence: 99%